Size dependent nature of the magnetic-field driven superconductor-to-insulator quantum-phase transitions - Xiaofu Zhang; Adriana E. Lita; Huanlong Liu; Varun B. Verma; Qiang Zhou; Sae Woo Nam; Andreas Schilling (Communications Physics, 2021)
The underlying mechanism of the superconducting-to-insulator transition under an applied magnetic field has been a topic of debate for many years. Here, the authors investigate the superconductor-to-insulator transition in 2D films and investigate the nature of the transition as a function of sample dimensions and reveal the importance of the quantum-Griffiths singularity.